A functional polymorphism in TFF1 promoter is associated with the risk and prognosis of gastric cancer. Issue 9 (20th December 2017) - Wang, Weizhi; Li, Zheng; Wang, Jiwei; Du, Mulong; Li, Bowen; Zhang, Lei; Li, Qing; Xu, Jianghao; Wang, Linjun; Li, Fengyuan; Zhang, Diancai; Xu, Hao; et al.
Abstract : Trefoil Factor 1 (TFF1, also named pS2), which serves as the gastrointestinal mucosal protector, is known as gastric‐specific tumor suppressor gene. However, the genetic variants of TFF1 are still not well studied. In our study, we aim to explore the effects of tagging single nucleotide polymorphisms (tagSNPs) of TFF1 on risk and prognosis of gastric cancer. Seven tagSNPs of TFF1 gene were first analyzed in the discovery set, which was consisted of 753 cases and 950 cancer‐free controls. Then, the validation set (940 cases and 1, 042 controls) was used for further evaluation. Moreover, we also tested the relation between these tagSNPs and prognosis of gastric cancer (GC). A series of experiments were performed to investigate the underlying mechanisms. We found that rs3761376 AA in the promoter region of TFF1, could reduce the expression of TFF1 by affecting the binding affinity of estrogen receptor 1 (ESR1, ERα), and thereby increased the risk of GC (1.29, 1.08–1.53). Moreover, the rs3761376 AA genotype was also found associated with worse prognosis among patients receiving 5‐FU based chemotherapy after surgery (1.71, 1.18–2.48). Further functional assays demonstrated that TFF1 could increase the chemosensitivity of 5‐FU by modulating NF‐κB targeted genes. These results identified the effect of rs3761376 on TFF1 expression, which accounted for the correlation with susceptibility and prognosis of GC; and this genetic variant may be a potential biomarker to predict the risk and survival of GC. Abstract : What's new? TFF1 is a well‐established gastric‐specific tumor suppressor gene, but the mechanisms underlying its expression and role in gastric tumorigenesis remain unclear. This study shows that rs3761376 AA in the promoter region of TFF1 can reduce TFF1 expression by affecting the binding affinity of estrogen receptor 1, thereby increasing the risk of gastric cancer. Moreover, rs3761376 AA was associated with worse prognosis among patients receiving 5‐FU based chemotherapy after surgery, with TFF1 increasing the chemosensitivity of 5‐FU by modulating NF‐κB targeted genes. The findings suggest that TFF1 rs3761376 may be used as a potential biomarker for gastric cancer diagnosis and prognosis.